Overview of Premarital Sex Behavior in Adolescents in Kupang Regency - Sang Ayu Made Sri Widyari; M. K. P. Abdi Keraf; Marleny P. Panis (Lembaga Dongan Dosen, 2025)
Adolescence is a transitional period from children to adults which includes all the development experienced in preparation for entering early adulthood. Premarital sex is very prevalent among teenagers because of the lack of proper guidance and information, it is feared that they have a wrong assumption about problems that are pleasing to sex and it will be more dangerous if such a situation is allowed continuously, then premarital sex behavior will become something common for teenagers. This study aims to find out the description of premarital sex behavior in adolescents in Kupang Regency. The research method used is descriptive qualitative research. Data collection was carried out using interview techniques using interview guidelines. The subjects in this study were taken based on certain criteria using the purposive sampling technique. The participants in this study were 5 adolescents aged 17-19 years. The results of this study show that premarital sex behavior in adolescents has become common. The reason teenagers engage in premarital sex is because of high curiosity and affection and fear of loss. Teenagers have done a series of stages of premarital sex such as holding hands, kissing, oral sex, and having sex. Factors that influence adolescents to have premarital sex include; the influence of social media, peers, and having disharmonious relationships and lack of attention from parents.